2011
DOI: 10.1136/vr.d4471
|View full text |Cite
|
Sign up to set email alerts
|

Severe oxalate nephropathy in Zwartbles sheep

Abstract: On the basis of the epidemiological findings, we believe that some Zwartbles sheep may have an inherited predisposition to develop pronounced renal oxalate crystal deposition, resulting in a chronic progressive nephropathy. Primary hyperoxaluria is well recognised in human beings (Bobrowski and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…The indings indicated oxalateassociated nephropathy, which has previously been reported in zwartbles sheep in the UK and is believed to have a hereditary component. 4,5…”
Section: Renal Diseasesmentioning
confidence: 99%
“…The indings indicated oxalateassociated nephropathy, which has previously been reported in zwartbles sheep in the UK and is believed to have a hereditary component. 4,5…”
Section: Renal Diseasesmentioning
confidence: 99%
“…Large numbers of oxalate crystals, in addition to tubular dilatation consistent with ‘drunken lamb syndrome’, were seen histologically. Congenital oxalate‐associated nephropathy was suspected, despite the young age of the lamb (Strugnell and others 2011, Barley and others 2015).…”
Section: Small Ruminantsmentioning
confidence: 99%
“…In cattle, rare cases of neonatal oxalate nephropathy in purebred calves with no known exposure to exogenous oxalates were reported [ 4 , 5 ]. In Zwartbles sheep, severe oxalate nephropathy was previously described with suspicion of hereditary predisposition on the basis of epidemiological findings in Great Britain and Northern Ireland [ 6 , 7 ]. The observed age of onset was quite variable (three weeks to three years) but the clinical signs and histopathology were similar in all the studied cases [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Zwartbles sheep, severe oxalate nephropathy was previously described with suspicion of hereditary predisposition on the basis of epidemiological findings in Great Britain and Northern Ireland [ 6 , 7 ]. The observed age of onset was quite variable (three weeks to three years) but the clinical signs and histopathology were similar in all the studied cases [ 6 ]. The prevalence of PH in sheep has not been studied prospectively, but data from the 2002–2009 period suggested that the incidence of all forms of urinary system disease in Zwartbles sheep is higher (7.2%, 13/179 submissions) compared to all other breeds (0.86%, 909/105,176 submissions) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation